CS08 | A combination of two rapid immunoassays improves HIT diagnosis (Bleeding, Thrombosis and Vascular Biology, 2025)
Background and Aim: Heparin induced thrombocytopenia (HIT) is an immune adverse reaction induced by the exposure to heparin which leads to the production of IgG antibodies against heparin-platelet factor 4 (H-PF4) complexes. The diagnosis is suspected based on a clinical evaluation with the 4T pre-test probability score (4Tscore) and required the detection of circulating antibodies bound to H/PF4 complexes by immunological and functional assay. Immunological assays are easy to perform, widely available and show high sensitivity. Functional assays are the gold standard for HIT diagnosis after a positive immunological test. However functional tests are technically demanding, time-consuming and limited to few, expert laboratories. This study aims to evaluate the performance of a combination of two automated rapid immunoassays -LIA and CLIA -with respect to the gold standard: an immunoassay -CLIA- followed by functional test -HIPA- for HIT diagnosis.